Is acromioplasty necessary in the setting of full-thickness rotator cuff tears? A systematic review - Familiari, Filippo (J Orthop Traumatol, 2015)
BACKGROUND: The benefits of acromioplasty in treating rotator cuff disease have been debated. We systematically reviewed the literature regarding whether acromioplasty with concomitant coracoacromial(CA) release is necessary for the successful treatment of full-thickness rotator cuff tears. MATERIALS AND METHODS: We identified randomized controlled trials that reported on patients who underwent rotator cuff repair with or without acromioplasty and used descriptive statistics to summarize the findings. RESULTS: Four studies fulfilled the inclusion criteria. They reported on 354 patients (mean age, 59 years; range 3–81 years) with a mean follow-up of 22 months (range 12–24 months). There were two level-I and two level-II studies. Two studies compared rotator cuff repair with versus without acromioplasty, and two studies compared rotator cuff repair with versus without subacromial decompression (acromioplasty, CA ligament resection, and bursectomy). The procedures were performed arthroscopically, and the CA ligament was released in all four studies. There were no statistically significant differences in clinical outcomes between patients treated with acromioplasty compared with those treated without acromioplasty. CONCLUSIONS: This systematic review of the literature does not support the routine use of partial acromioplasty or CA ligament release in the surgical treatment of rotator cuff disease. In some instances, partial acromioplasty and release of the CA ligament can result in anterior escape and worsening symptoms. Further research is needed to determine the optimum method for the operative treatment of full-thickness rotator cuff tears. LEVEL OF EVIDENCE: Level I, systematic review of level I and II studies.